Distribución de aves acuáticas en las lagunas de oxidación de la ciudad de La Paz, Baja California Sur, México - Margarita Zamora Orozco, Elvia (2007)
axonomic composition, spatial and temporal distribution of aquatic birds in oxidation lagoons (LO) of La Paz city in south Baja California, Mexico, were determined during 24 censuses realized in two-week intervals (April/98-March/99). There are five lagoons of 5 Ha each and 17 ha of terrains constantly flooded that serve as feeding areas for cattle and birds. One hundred twenty three species were observed, 75 of which were aquatic birds. A total of 46 041 observations were made (average 1 918 birds/census). Richness and abundance of aquatic birds were influenced mainly by migration of anatids and sandpipers. The first group had the great-est abundance due to its affinity towards fresh water bodies. The terrains were the favorite sites of dabbling ducks (Anas) and sandpipers. in contrast, two of the most abundant species (Oxyura jamaicensis, 12.5 % of all species, and Fulica americana, 8.8 %) restricted their presence to the oxidation lagoons. LO presented a bird structure of its own and atypical, according to the dryness of the region.